1983
DOI: 10.1080/03014468300006771
|View full text |Cite
|
Sign up to set email alerts
|

Lung function in an Australian population: contributions of polygenic factors and thePilocus to individual differences in lung function in a sample of twins

Abstract: A study of lung function in 203 twin pairs aged 18-34 years living in Sydney detected significant genetic variation in females and males. There was no evidence of family environmental effects in either sex and most of the repeatable variation in females was heritable. However, there was evidence for systematic environmental differences between males affecting lung function so that the heritability was lower in males (about 0.6) than females (about 0.8). An effect of smoking on lung function was detected but ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1985
1985
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…More recently, studies of general twin populations have suggested that genetic factors are of importance in individual differences in lung function [4,6,20], and family studies have shown that relatives of subjects with COPD had a higher risk of airflow obstruction than controls [21-23]. In another study of unselected elderly twins in the Swedish twin registry [6], heritability estimates adjusted for smoking were lower for FEV 1 (24-41% vs. 67%) but more similar for VC (61% vs. 48%) than the current results.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, studies of general twin populations have suggested that genetic factors are of importance in individual differences in lung function [4,6,20], and family studies have shown that relatives of subjects with COPD had a higher risk of airflow obstruction than controls [21-23]. In another study of unselected elderly twins in the Swedish twin registry [6], heritability estimates adjusted for smoking were lower for FEV 1 (24-41% vs. 67%) but more similar for VC (61% vs. 48%) than the current results.…”
Section: Discussionmentioning
confidence: 99%
“…A small negative correlation was found between BAC measures and lung volume. Since FVC is a good indicator of general physical health (Gibson et al, 1983), this correlation may reflect increased metabolic efficiency in the physically fit.…”
Section: Discussionmentioning
confidence: 99%
“…This was so irrespective of sex and absorption versus elimination. Age per se is not an inherited trait and weight, adiposity, and lung function are incompletely inherited (Clark et al, 1980;Gibson et al, 1983), so the contribution of these four variables to the heritable portion of total BAC variance must also have been small.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between males and females was attributable to environmental influences. 183 This study showed that ∼9% of the variance in women was associated with Pi polymorphism. No effect of the Pi locus was found in males.…”
Section: Genetic and Familial Factors In Decline In Lung Functionmentioning
confidence: 97%